Place Branding and Marketing from a Policy Perspective: Building Effective Strategies for Places - Vincent Mabillard; Martial Pasquier; Renaud Vuignier (Routledge, 2024)
As part of an emerging literature on place branding, this book fills the important gap between practice-oriented literature—which lacks in-depth and critical analysis—and technical academic literature—which tends to miss down-to-earth practitioners' concerns and to overlook policy and political contexts. Providing frameworks and knowledge on how to practice place branding effectively, this book anchors place-branding practices in a solid analytical framework. It presents place-branding practices through the lenses of public sector marketing, strategic management, and governance processes and structures, as well as communication tools. Marketing a place is more than creating a logo and a motto; this book presents the key strategic aspects to be considered when promoting a place. Readers will gain knowledge about the most important features of place promotion: the development of brands and marketing campaigns in the public sector, the establishment of dedicated politico-administrative structures, and the increasing involvement of various stakeholders that play a central role as place promoters. This book will be a valuable resource for researchers and postgraduate students across place branding, marketing and management, and urban studies, as well as public management, administration, and policy. The practical conclusions discussed in the book will also appeal to practitioners, business consultants, and people working in public administration and politics.
Keywords: 330; marketing; place management; place marketing; public sector marketing; strategic management